Characteristics and Hazards of Plug-In Hybrid Electric Vehicle Fires Caused by Lithium-Ion Battery Packs With Thermal Runaway - Cui, Yan; Cong, Beihua; Liu, Jianghong; Qiu, Mingming; Han, Xin (Frontiers in Energy Research, 2022)
Fire accidents constitute a significant safety concern for automotive lithium-ion battery packs and have impeded the development of electric vehicles (EVs). While fire safety concerns have been raised about EVs, their fire performance remains unknown, especially for plug-in hybrid electric vehicles (PHEVs). Hence, this paper conducted full-scale fire experiments of PHEVs to explore their fire behavior and characteristics. Two brand new PHEVs were employed, and their power battery packs were ignited as the origin of the fire to simulate the representative fire scenario. Results showed that visible flames appeared around the chassis after about 60 min of the experimental procedure. Around the fire emerged, the battery packs intermittently released plenty of white smoke, which induced gas-phase explosions. The main component of the smoke was combustible gases. The SUV-type PHEV test took 9 min 11 s for the chassis flames to evolve into a passenger compartment fire. Due to the slow propagation of the fire in sedan-type PHEV, it required 9 min 56 s for flames to engulf the rear part of the sedan. The maximum temperature of PHEV fires was 843.6 °C, while the maximum height of the fire reached around 3 m. At a distance of 1 m, the radiative heat emitted from burning PHEVs peaked at 1.151 kW/m2. Moreover, some secondary hazards of PHEV fires were illustrated. These results stimulate future experiments seeking novel flame retardant materials for PHEVs and provide helpful guidance on screening reliable PHEV fire prediction and protection strategies.